Investigation of reasons for decrease in mechanical characteristics of hot-rolled steel 09G2S bends - K. N. Pantyukhova; D. A. Negrov; O. Yu. Burgonova; V. Yu. Putintsev (Омский научный вестник: Серия "Общество. История. Современность")
In this paper, the causes of the drop in the mechanical properties in the process of manufacturing the «bend-out» part are investigated. On the basis of the obtained results, nonstandard heat treatment is proposed allowing to increase the mechanical characteristics to the initial values. Experimental data showing the validity of the proposed heat treatment regimes are given.